The efficacy of cognitive behavioral therapy for cancer: A scientometric analysis - Lin, Chuanghao; Tian, Huiting; Chen, Lingzhi; Yang, Qiuping; Wu, Jinyao; Ji, Zeqi; Zheng, Daitian; Li, Zhiyang; Xie, Yanna (Frontiers in Psychiatry, 2022)
Cognitive behavioral therapy (CBT) is one of the most recognized psychological interventions to improve the overall quality of life of cancer survivors. To analyze current research trends in the field of the link between cognitive behovioral therapy and cancer and to provide potential future research directions, we conducted the scientometric analysis. The study was conducted on all documents in this field from 2012 to 2022 retrieved from Web of Science. Then Biblioshiny, VOSviewer software, and CiteSpace software were used for getting the information of article postings and citations, countries, institutions, journals, authors, and keywords. The number of documents about the link between cognitive behavioral therapy and cancer from 2012 to 19 July 2022, was 619, with 476 of articles and 143 of reviews. The number of annual publications has been fluctuating, with the highest number of publications in 2020. The country with the maximum number of publications and citations was the US. The University of Houston was the organization with the highest quantity of publications and total link strength. Psycho-Oncology was the most active journal in the field and has the highest h-index. Zvolensky MJ was the author with the highest quantity of publications. The most cited keywords were "Quality-of-life", "Cognitive-behavioral therapy", " Depression", "Cognitive therapy" and "Breast-cancer". And as evidenced by the keyword citations, the focus of this research area has gradually shifted to the mental health of patients and the underlying pathogenesis. The impact of cognitive behavioral therapy in cancer treatment is now well established and has gradually evolved towards symptom-specific treatment. However, the relationship between cognitive behavioral therapy and cancer has not been further developed. Future research is needed to be further developed in the identification of a generic formula for cognitive behavioral therapy in cancer and the exploration of mechanisms of cognitive behavioral therapy and cancer.